2006
DOI: 10.1007/s10519-006-9113-4
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by Environment Interaction in Adolescents’ Cognitive Aptitude

Abstract: In a replication of Turkheimer, Haley, Waldron, D'Onofrio, Gottesman II (2003, Socioeconomic status modifies heritability of IQ in young children. Psychological Science, 14:623-628), we investigate genotype-environment (G × E) interaction in the cognitive aptitude of 839 twin pairs who completed the National Merit Scholastic Qualifying Test in 1962. Shared environmental influences were stronger for adolescents from poorer homes, while genetic influences were stronger for adolescents from more affluent homes. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
160
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(193 citation statements)
references
References 17 publications
27
160
6
Order By: Relevance
“…As a consequence, the well-established increase in heritability of IQ with age (21,22) will be driven by an even stronger increase in heritability of IQ within low-SES groups. This result would be consistent with the heritability measures for high-SES individuals being high already in childhood and adolescence (19,23).…”
Section: Meier Et Al 2012: Study Design and Methodological Issuessupporting
confidence: 87%
See 1 more Smart Citation
“…As a consequence, the well-established increase in heritability of IQ with age (21,22) will be driven by an even stronger increase in heritability of IQ within low-SES groups. This result would be consistent with the heritability measures for high-SES individuals being high already in childhood and adolescence (19,23).…”
Section: Meier Et Al 2012: Study Design and Methodological Issuessupporting
confidence: 87%
“…As a consequence, the well-established increase in heritability of IQ with age (21, 22) will be driven by an even stronger increase in heritability of IQ within low-SES groups. This result would be consistent with the heritability measures for high-SES individuals being high already in childhood and adolescence (19,23).It is worth noting that the relationship between SES and IQ change is supported empirically and has validity independently of the Flynn-Dickens theory that led us to it. Empirical research on how IQ trajectories differ with individual characteristics indicates that age-related cognitive decline is higher for some minorities, those with low education, and those in jail (24,25).…”
supporting
confidence: 80%
“…It has been demonstrated that a large sample is necessary to detect C , and the present study may lack sufficient power. Studies of heritability of cognition have found that there is a gene 3 environment interaction such that shared environmental factors become more prominent relative to genetic factors as socioeconomic conditions worsen [Harden et al, 2007;Turkheimer et al, 2003]. The subjects in the current study came primarily from middle to high socioeconomic settings.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies report differences between groups that vary in dominance, for example between the ages and sexes, but some studies have explicitly shown a negative correlation between innovativeness and competitive ability over and above these dominance groups [39]. Although these effects tend to be interpreted as environmentally mediated, a gene  environment interaction cannot be easily ruled out since additive genetic differences may only be apparent at a specific age or in a specific environment [64,65]. Clearly, in addition to the possibility that innovativeness has a heritable component of variation, a range of environmental factors are also likely to explain the tendency to innovate but the importance of these in natural populations has not been tested.…”
Section: Introductionmentioning
confidence: 99%